Breaking in or breaking down?: Culture shock among Filipino Freshmen students in a state university - Abarientos, Kenna; Ancho, Inero; Recto, Ferlynn B.; Saguiguit, Sue Liza; Pelegrina, Daisy (Research and Social Study Institute, 2025)
This study investigates the phenomenon of culture shock among freshmen students at a Philippine state university, where education is highly valued as both a familial legacy and a personal investment. Using a phenomenological approach, the study explores the lived experiences of ten high-achieving freshmen living independently at a state university in Laguna, Philippines. Thematic analysis reveals profound academic and social challenges impacting students’ academic performance, acculturation, and overall well-being. These challenges include: (1) Navigating a new academic environment and rigor, (2) Mastering time management and navigating lifestyle adjustments, (3) Managing finances and maintaining scholarships, (4) Adapting socially and culturally, (5) Managing expectations and pressure, and (6) Challenges to psychological and emotional well-being. Furthermore, the study identifies key coping strategies employed by these students, including seeking support networks – family, friends, peers, organizations, and scholarships – and developing personal adaptive mechanisms, primarily relying on self-help. These findings highlight the multifaceted nature of culture shock and offer valuable insights for university policies aimed at supporting incoming students’ cultural and academic adjustment.